PROPOSITION-BASED EVALUATION OF MACHINE-TRANSLATED ACADEMIC TEXT - Aulia Addinillah Arum; B.R. Suryo Baskoro (Universitas Islam Sumatera Utara (UISU), 2022)
This study aims to describe the rendition of propositional meaning in machine-translated academic text. A proposition is that part of the meaning of a clause or sentence that is constant, despite changes in such things as the voice or illocutionary force of the clause. A proposition may be related to other units of its kind through interpropositional relations, such as temporal relations and logical relations. To assess whether the meaning of an utterance is conveyed adequately in the target text, we conducted the proposition-based evaluation by looking at the grammatical structure, semantic roles, and the category of proposition reflected in the source text and the target text. The analysis is done by adopting the qualitative approach based on Larson’s theory of Meaning-Based Translation. The findings of this study suggest that identical grammatical structure can have a positive correlation to the semantic structure and the transfer of meaning in machine translation. This study also reveals that grammatical-structure similarity does not always indicate meaning accuracy in translation.